Ex 8.3
Ex 8.3, 2 Important
Ex 8.3, 3 (i) [MCQ]
Ex 8.3, 3 (ii) [MCQ] Important
Ex 8.3, 3 (iii) [MCQ] Important
Ex 8.3, 3 (iv) [MCQ]
Ex 8.3, 4 (i) Important
Ex 8.3, 4 (ii)
Ex 8.3, 4 (iii) Important
Ex 8.3, 4 (iv) Important
Ex 8.3, 4 (v) Important
Ex 8.3, 4 (vi)
Ex 8.3, 4 (vii) Important
Ex 8.3, 4 (viii)
Ex 8.3, 4 (ix) Important
Ex 8.3, 4 (x) You are here
Question 1 (i) Important
Question 1 (ii)
Last updated at Dec. 16, 2024 by Teachoo
Prove the following identities, where the angles involved are acute angles for which the expressions are defined. ((1 +π‘ππ2 π΄)/(1 + πππ‘2 π΄))=((1 βtanβ‘γ π΄γ)/(1 βcotβ‘ π΄))^2=π‘ππ2 π΄ Solving ((π + ππππ π¨)/(π + ππππ π¨)) ((1 + π‘ππ2 π΄)/(1 + ππππ π΄)) = ((1 + π‘ππ2 π΄))/(((1+ π/(ππππ π¨)) ) = ((1 + π‘ππ2 π΄))/(((tan^2β‘π΄ + 1))/(tan^2β‘π΄ ))= (π‘ππ2 π΄ (1 + π‘ππ2 π΄))/((π‘ππ2 π΄ + 1)) = tan2 A = R.H.S Solving ((πβ πππβ‘π¨)/(πβ πππβ‘π¨ ))^π ((1β tanβ‘π΄)/(1β πππβ‘π¨ ))^2 = ((1 β tanβ‘γ π΄γ)/(1 β π/πππβ‘γ π¨γ ) " " )^2 = (((1 β tanβ‘γ π΄)γ)/(((tanβ‘γ π΄ β1γ ))/tanβ‘γ π΄γ ))^2 = (tanβ‘γ π΄(1 β tanβ‘γ π΄)γ γ/( (tanβ‘γ π΄ β1)γ ))^2 = (tanβ‘γ π΄(1 β tanβ‘γ π΄)γ γ/(β(1 β tanβ‘γ π΄)γ ))^2 = (βtanβ‘π΄ )^2 = tan2 A = RHS Therefore, ((1 + π‘ππ2 π΄)/(1 + πππ‘2 π΄))=((1 β tanβ‘γ π΄γ)/(1 β cotβ‘ π΄))^2=π‘ππ2 π΄ H\ence proved